Capital theory and the distribution of income - Bliss, C. J. (Amsterdam : North-Holland Pub. Co. ; New York : American Elsevier, 1975)
The book first takes a look at production without capital, equilibrium, prices, and time, and semi-stationary growth, as well as the existence of constant-rate-of-interest price systems. The manuscript then discusses marginal products and capital and the Cambridge model. The text examines the aggregation of miscellaneous objects, production function, linear production model, and efficiency, production prices, and rates of return, as well as prices and efficiency for infinite developments. The manuscript also ponders on investment, structure of interest rates, and disputations. Discussions focus on sets and convex sets, concave functions, and linear and non-linear programming. The publication is a dependable source of data for economists and researchers interested in capital theory and the distribution of income.
Includes index.
Bibliography: p. [367]-372.
rpm 10/11/2017
Loans
Keywords: Capital; Capital theory; Income distribution